Selection of Donor-Recipient Pairs in Renal Transplantation: Comparative Simulation Results - Lima, Bruno Alves (2017)
Introduction: Implemented in 2007 by Ordinance No. 6357, allocation rules of cadaveric donor kidneys seek to distribute equitably a scarce community resource to patients who can improve their survival and quality of life. As stated in the aforementioned ordinance these rules must be updated whenever the state of the art recommends it. The objective of this work is to evaluate and compare three cadaveric donor allocation models: scoring criteria of ordinance nº 6537/2007 (model 1); similar to the previous model but with a lower score for the dialysis time (model 2); and a model adapted from the previously proposed color allocation system (model 3).Material and Methods: For the purpose of this analysis we generated data about 70 cadaveric donors taking into account information published regarding blood group distribution and human leucocyte antigens allelic and haplotype frequencies of Portuguese voluntary donors. We generated also data for a simulated waiting list of 500 first-time kidney transplant candidates.Results: We observed fewer candidates selected by model 3 with more than 3 human leucocyte antigens mismatches (39.3%) when compared to those selected by model 1 with more than 3 human leucocyte antigens mismatches (57.1%, p < 0.01).Discussion: In our analysis, model 3 selects transplant candidates with a lower number of human leucocyte antigens mismatches when compared to the adapted rules for kidney allocation of Ordinance No. 6537/2007 (model 1) without penalizing candidates with a longer time on dialysis.Conclusion: The analysis and discussion of the best rules for allocation of such a scarce resource as organs from deceased donors should be a continuous and adaptive process inherent to transplant candidate’s waiting list evolution and mutation.